Perilaku Konsumen Terhadap Minat Pembelian Di Toko Sport Dari Konvensional Ke Online Shopping - Indriani, Agustina; Haholongan, Rutinaias; Dordia, Jihan Nabilah; Nur’aini, Nur’aini; Bila, Zakiya Salsa; Ananda, Lutfianita Poppie Dea; Ferdiansyah, Muhammad (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024), 2024)
This research aims to determine and analyze consumer behavior towards conventional sports shops which are entering the era of digitalization with e-commerce. This l research uses l the Purposive l Sampling method l with a qualitative approach. The l population in l this research are l consumers who l carry out online transactions l in l e- l commerce. Data l was obtained using l interviews and l documentation. Based l on the l results and discussion, it l shows that l sports shop consumers, that most consumers have made transactions via online media. Consumers feel many advantages when shopping online, including, it is more time efficient, there are many product variants and they can communicate at the same time but with various advantages, there are also disadvantages of online shopping, namely you cannot l see the physical l condition of l the goods l directly, while offline shopping you can see the goods. directly. Informants will carry out more sports equipment transactions online than conventionally   Keywords : Consumer Behavior, Conventional Marketing, Online Shopping, sports shop